BIOSORPTION OF METHYLENE BLUE BY WASTE APRICOT SHELLS FROM FOOD INDUSTRY - Tatjana Šoštarić; Marija Petrović; Jelena Milojković; Jelena Petrović; Marija Stanojević; Časlav Lačnjevac; Mirjana Stojanović (Journal of Engineering & Processing Management, 2015)
In this paper, the removal of methylene blue (MB) from aqueous solution by biosorption ontoapricot shellshas been investigated through batch experiments. Apricot shells were chosen as alocally available and abundant waste from fruit juice industry. Methylene blue is common pollutantof waste waters from textile industry.The influence of initial MB concentration on biosorption process has been studied. Theexperimental data have been analysed using Langmuir and Freundlichisotherm models. TheLangmuir model better fits to experimental data, which explain monolayer adsorption. Maximumbiosorption capacity is 24,31 mg/g. A comparison of the biosorption capacity of waste apricot shellswith biosorption capacities of similar adsorbents previously investigated indicates that apricotshells could be a promising biosorbent for removal of MB from aqueous solution.
Keywords: biosorption; apricot shells; methylene blue